2018
DOI: 10.2147/opth.s185052
|View full text |Cite
|
Sign up to set email alerts
|

The burden of neovascular age-related macular degeneration: a patient’s perspective

Abstract: PurposeTo quantify the burden and quality of life of patients and their caregivers in a cohort of patients with neovascular age-related macular degeneration (nAMD) in an Australian clinical setting.MethodsA total of 103 patients undergoing anti-vascular endothelial growth factor (VEGF) therapy for nAMD were asked to complete questionnaires relating to the financial and time burdens of nAMD.ResultsAll patients completed the questionnaires. Loss in productivity due to attendance of appointments was 4.4±1.7 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 34 publications
3
86
0
5
Order By: Relevance
“…27 The NEI-VFQ-25 scores reported herein were also lower (ie, poorer) than previously reported in patients with neovascular AMD in two ranibizumab clinical trials (MARINA and ANCHOR) at baseline, as well as in a cross-sectional, non-interventional study in patients undergoing anti-vascular endothelial growth factor therapy. 25,28 In line with our NEI-VFQ-25 findings, patients with GA were found to have poorer VA at study entry than those without GA, with the majority of patients in the GA group having moderately low vision or blindness in one or both eyes. One in 5 of the patients with GA were either registered as blind or undergoing the registration process, which supports previous findings from a UK EMR study in which 7.1% were eligible for blindness registration in the United Kingdom at diagnosis, with a further 16% being eligible as vision impairment increased over time (median time to outcome, 6.2 years).…”
Section: Discussionsupporting
confidence: 73%
“…27 The NEI-VFQ-25 scores reported herein were also lower (ie, poorer) than previously reported in patients with neovascular AMD in two ranibizumab clinical trials (MARINA and ANCHOR) at baseline, as well as in a cross-sectional, non-interventional study in patients undergoing anti-vascular endothelial growth factor therapy. 25,28 In line with our NEI-VFQ-25 findings, patients with GA were found to have poorer VA at study entry than those without GA, with the majority of patients in the GA group having moderately low vision or blindness in one or both eyes. One in 5 of the patients with GA were either registered as blind or undergoing the registration process, which supports previous findings from a UK EMR study in which 7.1% were eligible for blindness registration in the United Kingdom at diagnosis, with a further 16% being eligible as vision impairment increased over time (median time to outcome, 6.2 years).…”
Section: Discussionsupporting
confidence: 73%
“…The literature review also identified studies that examined potential barriers to treatment, though these did not specifically address how these barriers correlated to adherence or persistence. 41 , 45 , 46 , 47 Additional risk factors reported in these studies include the differences in perceived treatment burden by patients or their caretakers of the various injection regimens, with lower burden index for patients on T&E regimen as compared to PRN, 45 and PRN more favourable as compared to monthly. 48 However, treating ophthalmologists reported difficulties of some patients in understanding the proactive nature of T&E regimens.…”
Section: Resultsmentioning
confidence: 99%
“… 47 Socioeconomic factors were also prominent in these studies with caretaker productivity loss (both time and financial) a significant burden. 45 , 46 Overall, treatment burden, both in terms of visit frequency and travel time was cited as the most significant barrier. 46 …”
Section: Resultsmentioning
confidence: 99%
“…Due to the chronic nature of anti‐VEGF therapy, average annual out‐of‐pocket costs for nAMD or DMO patients typically exceed this level. Spooner et al reviewed the financial burden associated with intravitreal assessment and injections for 103 consecutive nAMD patients at a private clinic in Sydney and reported an average annual direct cost to patient of $2784 …”
Section: Introductionmentioning
confidence: 99%